2018
DOI: 10.15171/hpr.2018.03
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Contraceptive Preferences Among Postpartum Women in Izzi, Ezza South, and Ikwo Local Government Areas of Ebonyi State, Nigeria

Abstract: BackgroundIn Nigeria, the fertility rate is high and the contraceptive prevalence rate is very low.1 Therefore, women in Nigeria are exposed to the dangers of unwanted and unplanned pregnancies. In Ebonyi State, Nigeria, the demand for family planning is about 15%, while the unmet need for contraceptives among women who are currently married is 30%.2 Contraceptive use for spacing the births of children is 13.1%, while contraceptive use for limiting the number of children in a family accounts for 7.5%. 2 The ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Furthermore, postpartum mothers who were counseled during their postnatal care visit were nearly 4-times more likely to have good knowledge on postpartum contraceptive use compared to those mothers who were not counseled. This finding is supported by reports from Nigeria 24 and India. 35 This is because women who received family planning counseling during PNC might have adequate information regarding the source, benefit, side-effect, of contraceptives, and the place where they could find contraceptives.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, postpartum mothers who were counseled during their postnatal care visit were nearly 4-times more likely to have good knowledge on postpartum contraceptive use compared to those mothers who were not counseled. This finding is supported by reports from Nigeria 24 and India. 35 This is because women who received family planning counseling during PNC might have adequate information regarding the source, benefit, side-effect, of contraceptives, and the place where they could find contraceptives.…”
Section: Discussionsupporting
confidence: 87%
“…The questionnaire was adapted from EDHS and other published literature. [24][25][26][27] The questionnaire includes socio-demographic, reproductive health, and obstetric factors, source of information, and knowledge of modern postpartum contraceptives. Six female diploma midwives were assigned as data collectors and two Bsc nurses as supervisors.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Furthermore, it is important to note that, although sexual relationships, pregnancy and childbirth are necessary and cannot be avoided, the social and cultural environment also determines the attitude and preferences of women regarding contraception methods. 9 This study was undertaken with the objective to determine the awareness and acceptance status about various contraceptive methods among post-partum women in the tertiary care centre of Chhattisgarh.…”
Section: Introductionmentioning
confidence: 99%
“…A published work from Ebonyi State, Nigeria, indicated that postpartum women have a favourable attitude towards contraception. 13 Similarly, a study in Iran revealed that among postpartum women the intervention group had a higher positive attitude towards contraceptives than their counterparts in the control group (p < 0.05). 14 In Uganda, 71.4% of women in the control group and 87% in the intervention group intended to use a modern contraceptive method following counselling on PPFP.…”
Section: Introductionmentioning
confidence: 96%